On the implementation of the circular economy route for E-waste management: A critical review and an analysis for the case of the state of Kuwait - Al-Salem, Sultan Majed; Leeke, Gary Anthony; El-Eskandarani, Mohammed Sherif; Van Haute, Maarten; Constantinou, Achilleas; Dewil, Raf; Baeyens, Jan (My University, 2022)
Electronic waste (e-waste) has become one of the major causes of environmental concerns due to its large volume, high generation rate and toxic environmental burdens. Recent estimates put e-waste generation at about 54 million tonnes per annum with figures reaching approximately 75 million tonnes per annum by 2030. In this manuscript, the state-of-the-art technologies and techniques for segregation, recovery and recycling of e-waste with a special focus on the valorisation aspects of e-plastics and e-metals which are critically reviewed. A history and insight into environmental aspects and regulation/legislations are presented including those that could be adopted in the near future for e-waste management. The prospects of implementing such technologies in the State of Kuwait for the recovery of materials and energy from e-waste where infrastructure is lacking still for waste management are presented through Material Flow Analysis. The information showed that Kuwait has a major problem in waste accumulation. It is estimated that e-waste in Kuwait (with no accumulation or backlog) is generated at a rate of 67,000 tpa, and the imports of broadcasting electronics generate some 19,428 tonnes. After reviewing economic factors of potential recovered plastics, iron and glass from broadcasting devices in Kuwait as e-waste, a total revenue of $399,729 per annum is estimated from their valorisation. This revenue will open the prospect of ventures for other e-waste and fuel recovery options as well as environmental benefits and the move to a circular economy.
Keywords: E-Waste; E-Plastics; MFA; Kuwait; Recycling